Phonics Method Resolves Early Reading Difficulties In Elementary School Students: Metode Fonik Menyelesaikan Kesulitan Membaca Permulaan Pada Siswa Sekolah Dasar - Nurfadhila R.; Hermanto Hermanto (Academia Open, 2026)
General Background Early reading forms the fundamental basis for overall academic achievement, yet foundational literacy challenges remain prevalent in primary education. Specific Background At SDN 003 Teluk Pandan, several second-grade pupils demonstrate severe literacy deficiencies, particularly in letter-sound recognition and syllable blending, resulting in low diagnostic assessment scores. Knowledge Gap Although phonics instruction proves successful for specific cognitive disabilities like dyslexia, its systematic application for regular pupils experiencing general literacy deficits remains insufficiently explored. Aims This study investigates the application of a structured phonetic approach to build fundamental literacy proficiencies among second-grade pupils experiencing learning challenges. Results Utilizing a Kemmis and McTaggart Classroom Action Research design across two cycles with five participants, the analysis revealed a steady score progression from 49.7 to 73.2, with all participants eventually satisfying the minimum mastery criterion. Novelty This research distinctly integrates structured instructional phases, such as targeted blending and interactive word-building activities, to provide individualized scaffolding within a regular inclusive classroom environment. Implications Deploying explicit letter-sound instruction alongside interactive visual media serves as a highly supportive pedagogical framework for resolving fundamental literacy deficits and cultivating active pupil participation. Highlights Classroom action research across two instructional cycles demonstrated a mean score progression from 49.7 to 73.2. Targeted pedagogical interventions successfully guided all participating second-grade pupils to achieve minimum learning mastery standards. Structured letter-sound exercises and interactive word-building games stimulated active participation and peer collaboration during literacy tasks. Keywords Phonics Method; Early Reading Skills; Reading Difficulties; Classroom Action Research; Elementary School Education